First use of G-CSF in chlorpromazine-induced agranulocytosis: a report of two cases. Issue 817 (November 1993) - Kendra, J. R.; Rugman, F. P.; Flaherty, T. A.; Myers, A.; Horsfield, N.; Barton, A.; Russell, L.
Abstract : Chlorpromazine-induced agranulocytosis is an uncommon disorder associated with a high frequency of fatality. We describe two patients with chlorpromazine-induced granulocytosis in whom granulocyte colony stimulating factor (G-CSF) administration enhanced the speed of neutrophil recovery. No toxicity was noted with G-CSF and both patients made a successful recovery. We propose there is a role for such cytokine therapy in patients with life-threatening agranulocytosis in order to speed the recovery of neutrophils.